Antileishmanial Activity and In Silico Molecular Docking Studies of Malachra alceifolia Jacq. Fractions against Leishmania mexicana Amastigotes (2023)
ABSTRACT: Malachra alceifolia Jacq. (family Malvaceae), known as "malva," is a medicinal plant used as a traditional therapy in many regions of America, Africa and Asia. Traditionally, this plant is used in the form of extracts, powder and paste by populations for treating fever, stomachache, inflammation, and parasites. However, the ethnopharmacological validation of M. alceifolia has been scarcely researched. This study showed that the chloroform fraction (MA-IC) and subfraction (MA-24F) of the leaves of M. alceifolia exhibited a potential antileishmanial activity against axenic amastigotes of Leishmania mexicana pifanoi (MHOM/VE/60/Ltrod) and had high and moderate cytotoxic effects on the viability and morphology of macrophages RAW 264.7. This study reports, for the first time, possible terpenoid metabolites and derivatives present in M. alceifolia with activity against some biosynthetic pathways in L. mexicana amastigotes. The compounds from the subfractions MA-24F were highly active and were analyzed by gas chromatography-mass spectrometry (GC-MS) and by a molecular docking study in L. mexicana target protein. This study demonstrates the potential modes of interaction and the theoretical affinity energy of the metabolites episwertenol, α-amyrin and methyl commate A, which are present in the active fraction MA-24F, at allosteric sites of the pyruvate kinase, glyceraldehyde-3-phosphate dehydrogenase, triose phosphate isomerase, aldolase, phosphoglucose isomerase, transketolase, arginase and cysteine peptidases A, target proteins in some vital biosynthetic pathways were responsible for the survival of L. mexicana. Some phytoconstituents of M. alceifolia can be used for the search for potential new drugs and molecular targets for treating leishmaniases and infectious diseases. Furthermore, contributions to research and the validation and conservation of traditional knowledge of medicinal plants are needed globally.